Physicians Controlling Women’s Reproductive Choices: The Slow Liberalization of Abortion Laws in Finland - Takala, Tuija (Cambridge quarterly of healthcare ethics, 2023)
This paper provides an overview of the development and the sociopolitical background of legislation pertaining to abortion in Finland from the nineteenth century to the current day. The first Abortion Act came to force in 1950. Before that, abortions were handled under criminal law. The 1950 law was restrictive and allowed abortions in very limited circumstances only. Its main aim was to reduce the number of abortions and especially illegal abortions. It was not very successful in reaching these goals, but, significantly, it moved abortions from the realm of the criminal law to the hands of medical professionals. The birth of the welfare state and the prenatal attitudes of 1930s and 1940s Europe played their part in shaping the law. By late 1960s, with the rise of the women’s rights movement and other changes in society, there was pressure to change the outdated law. The new 1970 Abortion Act was broader and allowed abortions for limited social reasons too but left very limited, if any, room for a woman’s right to choose. After a citizen’s initiative in 2020, the year 2023 will see a significant amendment to the 1970 law; during the first 12 weeks of pregnancy, an abortion can be performed on the woman’s request alone. However, there is still a long way to go in terms of women’s rights and abortion laws in Finland.